The Concept and Understanding of Synchronous Stability in Power Electronic-Based Power Systems - Yayao Zhang; Miao Han; Meng Zhan (Energies, 2023)
Synchronous stability in power systems is of essential importance for system safety and operation. For the phase-locked loop (PLL)-based synchronous stability in power electronic-based power systems, which has recently stimulated interest in researchers in the field of electrical power engineering, but is still controversial, this paper divides the topic into two aspects, including the PLL device stability and the system stability. It is found that the PLL device is always stable and the error between the PLL output angle <semantics>θpll</semantics> and the terminal voltage angle <semantics>θt</semantics> is always finite. Therefore, the synchronization of power electronic-based power systems should be understood as the output synchronization between the electrical rotation vectors (<semantics>θt</semantics> or <semantics>θpll</semantics>) from each item of grid-tied equipment, rather than the synchronization of the PLL device itself. In addition, it is found that <semantics>θpll</semantics> plays an active role in the system synchronization dynamics not only in electromagnetic timescales but also electromechanical timescales and it could be selected as a dominant observable. In this paper, the concept of synchronous stability is well clarified. These findings are well supported by theoretical analyses and MATLAB/Simulink simulations, and thus could provide insights on the synchronous stability mechanism.